Given if
2y + 3x = 22,
x + y = 9.
Find xy
Note: This question has been edited for clarity. Previously, it seemed to state 2 y + 3 x = 2 2 x + y = 9 instead of 2 separate equations.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is a system of equations: 2 y + 3 x = 2 2 → ( 1 ) x + y = 9 → ( 2 ) Substituting x = 9 − y into the first equation,we get; 2 y + 3 ( 9 − y ) = 2 2 → 2 y − 3 y + 2 7 = 2 2 → − y = 2 2 − 2 7 = − 5 → y = 5 Substituting y = 5 into the second equation,we get; x + 5 = 9 → x = 9 − 5 = 4 So x y = 4 × 5 = 2 0
2 y + 3 x = 2 ( x + y ) + x = 2 ( 9 ) + x = 2 2 ⟹ x = 4 , so y = 9 − x = 5
∴ x × y = 2 0
It was given that,
2 y + 3 x = 2 2 .............(1)
x + y = 9 .....................(2)
Now , from equation (2)
⇒ x + y = 9
⇒ x = 9 − y ...................(3)
Placing the value of x in equation (1) to find y
⇒ 2 y + 3 ( 9 − y ) = 2 2
⇒ 2 y − y = 2 2 − 2 7
⇒ y = 5
Placing the value of y in equation (3) to find x
⇒ x = 9 − 5
⇒ x = 4
Multiplying x and y
= x × y
⇒ 4 × 5 = 2 0
2y + 3x = 22 ----------------------------------- I
x + y = 9------------------------------------------II
Equ I - 2 * Equ II
2y + 3x = 22 ------------------------------------III
x = 4
y = 9 - 4
= 5
therefore x * y = 4 * 5 = 20
2y + 3x = 22 ----------------------------------- I
x + y = 9------------------------------------------II
Equ I - 2 * Equ II
2y + 3x = 22 ------------------------------------III
-2x - 2 y = - 18 ---------------------------------IV
x = 4
y = 9 - 4
= 5
therefore x * y = 4 * 5 = 20
Problem Loading...
Note Loading...
Set Loading...
A faster method would be
2 y + 3 x = 2 ( x + y ) + x = 1 8 + x = 2 2 ⇒ x = 4 , y = 5